Millenia literary Indie authors: A review of selected Indie novels (1990-2017) - Nurain Khoo Kian Hua; Sim, Susan Chee Cheang (Human Resource Management Academic Research Society, 2019)
According to John (1997), a novel is considered a "social symptom". Lucas's interpretation based on Jacques Lacan's concept that a work is a text of one's psyche is evident when the novel or literary work is scrutinized according to the changes in this case; the Indie literature of Malaysia. The latest literary phenomenon in Malaysia a “new” creative work that defies form but appears to be familiar. Although the works produced are novels and poems, they differ in form and content especially in the style of writing. According to Muhammad (2016), “Indie literature” is understood as a stream or culture that seeks freedom from any authority and mainstream. This definition is emphasized by mainstream Malay literary critics who view Malaysian Indie Literature as “protest literature” whose objective is freedom of expression. The majority of these literary works are written by young authors from between the ages of 20 and 35 years old. This research hopes to uncover the ideological aspect of Malaysian Indie Literature with the intent to move its definition from a binary opposite of mainstream Malay literature to a literary genre that should be regarded as a literary form through a textual analysis of a selected number of Malay Indie novels from 1990s until 2017. It is hoped that this article will reveal the purpose of novel creation according to the thoughts of the authors as reflected through the plot, themes, characters and messages that will throw light to the rise of Indie literature in the ethos of Malay Literature.